Demystifying Outcomes Assessment for International Educators - Butler, Paige E. (Journal of International Students, 2016)
Darla Deardorff’s new book Demystifying Outcomes Assessment for International Educators: A Practical Guide utilizes an applied approach to outcomes assessment in international education. Faculty and practitioners across international education programs and services will find significant value in the materials presented throughout the text.